Review of a 25-Year Experience in the Management of Ovarian Masses in Neonates, Children and Adolescents: From Laparoscopy to Robotics and Indocyanine Green Fluorescence Technology - Esposito Ciro; Coppola Vincenzo; Cerulo Mariapina; Del Conte Fulvia; Bagnara Vincenzo; Esposito Giorgia; Carulli Roberto; Benedetta Lepore; Marco Castagnetti; Gianluigi Califano; Maria Escolino (MDPI AG, 2022)
Background: Ovarian masses in pediatric populations are the most common abdominal masses in young girls. In neonates, the majority of masses are benign while in children and teen-agers the risk of malignancy exists. The aim of this study is to perform a 25-year experience retrospective analysis of clinical and therapeutic aspects of ovarian tumors in girls, in order to show how the development of minimally invasive technology has changed the management of this pathology. Methods: The records of patients under the age of 18 who were operated in three pediatric surgical units due to ovarian mass, in the last 25 years, were reviewed retrospectively. The study group comprised 147 patients operated between 1996 and 2021 with a diagnosis of ovarian masses. Data involved were demographical, surgical, follow-up and final diagnosis. We analyzed the type of surgical technique, intra-operative data (operative time, the use of different technologies), complications, length of stay and long-term follow-up. Based on these data, we assessed how the surgical approach to ovarian masses has changed in the last 25 years in newborns and young girls. Results: The patients ages ranged between 7 days and 15 years (median, 59 days). All the procedures were completed in laparoscopy or robotics without conversion in open surgery. One-hundred and eleven patients were neonates; they all had follicular cysts and they were all managed in laparoscopy using 1 or 3 trocars. In 80/111 patients (72%), a small part of ovarian parenchyma was saved; in 31/111 patients (28%), in which the ovarian parenchyma was not available, an ovariectomy was performed. Patients in which we saved a small part of ovary, at long term follow-up (minimum follow-up of 12 years) (29/80, 36%), developed a normal ovary at US control. Thirty-six were older patients. They had a histological diagnosis of benign (30) or malign (6) tumors. All the patients (8/36) with a pre-operative suspicion of ovarian malignancy received an ovariectomy and an adnexectomy using sealing devices. In the last 10 years in all the children, except neonates, we adopted sealing devices and, in the last 4 years, in 20 cases, we always adopted ICG fluorescence technology to check ovarian vascularization in case of torsion or to check lympho-nodes condition in case of malignancy. Conclusions: In neonatal ovarian cysts, surgical management remained unchanged and an ovarian sparing procedure is always indicated and the long-term follow-ups confirm this hypothesis. The principal innovation in this age period is the use of ICG fluorescence technology to check ovarian vascularization in case of torsion. In teenagers, the decision-making strategy is based on the tumoral markers and on the morphological aspects of the mass. Robotics cystectomy or ovariectomy now-days represents the safer and faster way to perform this. Sealing devices are essential tools for dissection and resection to avoid bleeding. ICG fluorescence technology in all ages is fundamental to check ovary vascularization after detorsion or to check lympho-node status in case of malignancy. All the suspected lesions have to be removed with an endo-bag.